Correction: Psychiatric disorders in children with 16p11.2 deletion and duplication - Niarchou, Maria; Chawner, Samuel J. R. A.; Doherty, Joanne L.; Maillard, Anne M.; Jacquemont, Sébastien; Chung, Wendy K.; Green-Snyder, LeeAnne; Bernier, Raphael A.; Goin-Kochel, Robin P.; Hanson, Ellen; Linden, David E. J.; Linden, Stefanie C.; et al. (Translational psychiatry, 2019)
One of the co-authors, Marianne B.M. van den Bree has had her name incorrectly abbreviated by citation manager. It was stated as “Bree MBMVD14”, but has been updated to “van den Bree, M.B.M.” in the HTML, PDF, and XML versions of this article.